Pengaruh Penerapan Realistic Mathematic Education berbantuan GeoGebra terhadap Kemampuan Berfikir Kreatif Siswa di Sekolah Menengah Pertama Islam Tarbiyatusshibyan - Hadi, Sopian; Andriani, Parhaini; Mahfudy, Sofyan (Mathematic Education Departement, State Islamic University of Mataram, 2025)
This study aims to determine the effect of the implementation of the Realistic Mathematics Education (RME) model assisted by GeoGebra on the creative thinking skills of junior high school students. The study used a quantitative approach with a posttest-only control group design. The subjects of the study were grade VIII students at SMP Islam Tarbiyatusshibyan Beremi who were divided into two groups, namely the experimental class that received learning with the RME model assisted by GeoGebra and the control class that used conventional learning. The instrument used was a descriptive test of mathematical creative thinking skills. The results of data analysis showed that there was a significant difference between the creative thinking skills of students in the experimental class and the control class. This shows that the implementation of RME assisted by GeoGebra has a positive effect on improving students' creative thinking skills. Thus, the RME learning model assisted by GeoGebra can be an effective alternative in improving the quality of mathematics learning at the junior high school level